Bilingual health care in Quebec: Public policy, vitality, and acculturation issues - Bourhis, Richard Y. (Accessibility and active offer: Health care and social services in linguistic minority communities, 2017)
Abstract The first part of this chapter offers the Interactive Acculturation Model (IAM), which provides an intergroup approach to minority/majority group relations in multilingual settings. The ethnolinguistic vitality framework is the first element of the IAM as it describes the relative strength and weaknesses of linguistic communities in contact. Four language policies regulating the status of linguistic communities constitute the key second element of the IAM. Third, the acculturation orientations of minority and majority group speakers are described as they interact to yield harmonious, problematic or conflictual intergroup relations. As an application of the IAM, the second part of the chapter analyzes bilingual health care policies for official language minorities in Canada and Quebec. A detailed analysis of bilingual health care institutions serving the English-speaking communities of Quebec closes with a case study of a recent Quebec Government health care law that threatened to undermine the institutional vitality of the Anglophone minority of Quebec. Key words: Interactive Acculturation Model (IAM), English-speaking communities of Quebec, health care policies.

Acculturation, vitality, and bilingual healthcare - Bourhis, Richard Y.; Montreuil, Annie (The Oxford handbook of acculturation and health, 2017)

Problématique générale : Enjeux de l’accessibilité et de l’offre active de sociaux et de santé au sein de la francophonie canadienne en situation minoritaire - Drolet, Marie; Bouchard, Pier; Savard, Jacinthe; Laforge, M.-J. (Accessibilité et offre active : Santé et services sociaux en contexte linguistique minoritaire, 2017)
Cette problématique générale vise tout d’abord à présenter un portrait global des communautés francophones en situation minoritaire (CFSM) au Canada. Nous présenterons aussi la problématique de l’accessibilité à des services sociaux et de santé en français en contexte linguistique minoritaire, l’importance de l’accès à des services dans la langue officielle de son choix et les principaux éléments qui justifient le fait d’offrir activement des services sociaux et de santé en français dans les CFSM. Nous établirons également les bases d’une définition de l’offre active et certains contours politiques et historiques qui façonnent les services sociaux et de santé en français en contexte francophone minoritaire. Cette problématique générale sera, par conséquent, une assise pour chacun des chapitres qui composeront cet ouvrage et en facilitera la compréhension.

English, French and official language minorities in Canada: Census of population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistics Canada, 2017)

Le français, l’anglais et les minorités de langue officielle au Canada : recensement de la population, 2016 (n°98-200-X2016011) - Lepage, Jean-François (Statistique Canada, 2017)

Health care professionals and official-language minorities in Canada, 2001 and 2011 (n°89-657-X 2017002) - Lepage, Jean-François; Lavoie, Émilie (Statistics Canada, 2017)